DETERMINATION OF HISTAMINE IN CANNED FISH PRODUCTS USING HIGH PERFORMANCE LIQUID CHROMATOGRAPHY (HPLC) AND ENZYME LINKED IMMUNOSORBENT ASSAY (ELISA) METHOD - Aminah, Siti
Background: Fish poisoning due to the release of histamine generally come from families scombroidae fish such as tuna (Thunnus spp) and mackerel (Scomber spp), so called Scombrotoxin Fish Poisoning (SFP). In addition, families of non-scombroidae such as sardine (Sardinella spp), salmon (Arripis truttaceus), skipjack, and „kembung?also commonly known as a cause of SFP. According to the United States of Food and Drug Administration (FDA), consumption of histamine in 50 mg/100 g fish will cause poisoning. Therefore, level of histamine more than 20 mg/100 g has forbidden to be consumed. Determination of histamine in food products requires a methods in accordance to the regulation. This study was aimed to verify and determine histamine in canned fish products by High Performance Liquid Chromatography (HPLC) and Enzyme Linked Immunosorbent Assay (ELISA) methods. Method: Histamine in canned fish samples were analyzed using HPLC Agilent 1260 Infinity Series VWD with Zorbax Eclipse Plus C18 column (4.6 x 100 mm, 5?m) and ultraviolet detector of 254 nm. Mobile phase was consisted of mixture of 0,01 M ammonium acetateacetonitrile (6:4). Flow rate was adjusted at 0.6 mL min -1 and column temperature was maintained at 30 ºC. Samples were prepared using derivatization with 2% solution of benzoyl chloride in acetonitrile. ELISA analysis was carried out using instrument Histamine Ridascreen® R-Biopharm Art No. R1604. Lot.12404. Result: Calibration curve of histamine using HPLC method showed the regression equation of y = 284.9204 x + 673.5903 and correlation coefficient of r = 0.9961. The limits of detection and limit of quantitation, were 7.62 and 23.09 µg g -1 , respectively. The precision of the method was shown in coefficient of variance value of 1.62% whereas accuracy was in value of recoveries of histamine standard addition from canned fish samples of 86.26 to 92.39%. Calibration curve for determination of histamine using ELISA method showed the regression equation of y = -1.7269 x + 1.6450 and correlation coefficient of r = -0.9927. The limits of detection and limit of quantitation, were 2.61 and 7.91 µg g -1 , respectively. The precision of the method was in coefficient of variance value of 5.33% whereas it?s accuracy was 81.32% of recovery. Based on the results, it was concluded that the proposed method can be applied for determination of histamine in canned fish samples. Concentration of histamine in sample using HPLC and ELISA method was 95.65±1,55 µg/g and 80.32±4,28 µg/g respectively.